Using the thin slices technique to assess interactional quality in early childhood education and care settings - Vinokic, Konstantin; Baron, Franka; Kunter, Mareike; Linberg, Anja; Begrich, Lukas; Kuger, Susanne (Frontiers in Education, 2024)
There are a variety of instruments for measuring interaction quality of Early Childhood Education and Care (ECEC) teachers. However, these instruments are extremely resource-demanding in terms of time and money. Hence, a more economical and yet accurate method for measuring interaction quality of ECEC teachers would be desirable. The so-called thin slices technique has been applied to observe, measure and predict human behavior with only minimal amounts of information. In a wide array of research domains, thin slices ratings (i.e., ratings based on first impressions) proved to be accurate. The present study explores the accuracy of thin slices ratings of interaction quality in toddler classrooms along two CLASS Toddler domains (Emotional and Behavioral Support and Engaged Support for Learning). Eight CLASS-certified raters assessed interaction quality based on 30-second classroom videos. The findings suggest predominantly good reliabilities of these ratings. Confirmatory factor analysis yielded evidence for construct validity, meaning that thin slices raters could differentiate between two domains of interaction quality. Further, thin slices ratings correlated, at least partly, with ratings based on full-length videos, indicating that thin slices raters and raters watching the full-length videos had a similar impression of interaction quality of ECEC teachers.